Gravar under kyrkmurar - Lovén, Christian; Gejrot, Claes (Hikuin, 2003)
Graves beneath church walls By Christian Lovén, with an appendix by Claes Gejrot Skeletons discovered beneath church walls are generally taken to be indications of an earlier wooden church at the site. This may not always be true. Canon law, as well as provincial legislations, stated that burials were only allowed at churches. However, canon law allowed for funerals to begin already when the church building was in the planning stages. Three Swedish and Finnish written sources are of interest. The Bishops’ Chronicle of Västergötland (c.1325) states that bishop Sigfrid (11th century) marked three church sites and inaugurated the church yards. Bishop Bengt (c.1150–1180) had several churches erected, and he endowed them. The important point is that the author of the chronicle differs between these activities. An early 16th century Finnish account of the erection of a chapel at Lokalaks, 50 km NW of Turku, begins with the inauguration of the cemetery in 1490, with mass held by the bishop. This was at the request of two local noblemen. After this (post hoc), the two men erected a wooden chapel at the site. The chapel is mentioned in 1512. Finally, in a letter issued in 1470, the bishop of Linköping promises indulgence to all who visit the newly consecrated cemetery at Forsvik and pray at the four crosses erected at the corners of the cemetery (see appendix). No church by this name is known to have existed, but the letter probably concerns Forsvik on the W shore of lake Vättern. These scarce sources confirm that cemeteries may be older than their churches. Normally, the stretches of intended walls would be avoided for funerals. But the erection of the church may have been delayed so much that the layout was forgotten or revised. Considering the number of unfinished projects that we can trace in medieval church buildings, these delays may have been common. This could explain some of the graves beneath church walls. The ultimate form of delay, abandonment of the intended church site, is what appears to have come to pass at Forsvik.